Light, materiality and senses - Kong, Wen Yi (2015)
The project explores the relation between light, materiality and sense with the interest in the nature and quality of material and its interaction with light. It is set out as part-experiment and part-installation that embodies the idea of displaying light and material in a space that engages the human senses. Questioning how the nature and quality of material together with light could possibly alter or affect perception of space. The intention is to communicate, often neglected, subtle qualities of material as the center of attention through the use of the translucent quality of porcelain to create a lighting installation.